The Energy Costs of Prematurity and the Neonatal Intensive Care Unit (NICU) Experience - John B. C. Tan; Danilo S. Boskovic; Danilyn M. Angeles (MDPI AG, 2018)
Premature neonates are in an energy deficient state due to (1) oxygen desaturation and hypoxia events, (2) painful and stressful stimuli, (3) illness, and (4) neurodevelopmental energy requirements. Failure to correct energy deficiency in premature infants may lead to adverse effects such as neurodevelopmental delay and negative long-term metabolic and cardiovascular outcomes. The effects of energy dysregulation and the challenges that clinicians in the Neonatal Intensive Care Unit (NICU) face in meeting the premature infant's metabolic demands are discussed. Specifically, the focus is on the effects of pain and stress on energy homeostasis. Energy deficiency is a complex problem and requires a multi-faceted solution to promote optimum development of premature infants.